Formation of a system for selection and further support of sportsly gifted children, taken into account of continuity and consistency of sports training - Dveyrina O.A. ,; Belyy K.V. ,; Lalochkin M.M. ,; Lalochkina A.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to development of proposals for the formation of a system of selection and further support of sports gifted children, taking into account the continuity and consistency of sports training. Methods and structure of the study. The protocol of expert analytical work included: purpose, objectives, methods (theoretical analysis and synthesis of scientific and methodological literature and documentary sources, a survey of regional executive authorities in the field of physical culture and sports, qualitative PESTEL and SWOT analysis), planned results, and also the scope of application of these results. The study was conducted during 2023 and covered 84 regions of the Russian Federation. More than 1,000 scientific articles in journals listed by the Higher Attestation Commission, dissertation research contained on the information portal of the Russian State Library, as well as publications in collections of conference materials were studied. Results and conclusions. The expert-analytical assessment of the individual components of the selection system and the analysis of their mutual influence made it possible to formulate proposals for the formation of a system of selection and further support of sports gifted children, taking into account the continuity and consistency of sports training. The technological feasibility of improving the selection system presupposes: the use of the achievements of modern functional diagnostic hardware and software systems; methodological support and practical application of model characteristics of young athletes preparedness in sports; introduction of scientifically based profiles of competitive exercises, providing for the possibility of differentiating control and transfer standards for retardants, mediants and accelerators; development of methodological recommendations on mechanisms and criteria for selecting gifted children in sports; distribution of functions of performers of each of the events in accordance with the level of organization of the performer, providing for the inclusion of these functions in the charter of performers; regulatory support.